Cartilage Endplate-Derived Stem Cells for Regeneration of Intervertebral Disc Degeneration: An Analytic Study - Jia Z; Liu D; Li X; Wen T; Li W (Dove Medical Press, 2023)
Zhiwei Jia,1 Donghua Liu,1 Xingxuan Li,1 Tianlin Wen,1 Wei Li2 1Department of Orthopedics, Dongzhimen Hospital, Beijing University of Chinese Medicine, Beijing, People's Republic of China; 2Department of Sports Medicine, Fourth Medical Center of PLA General Hospital, Beijing, People's Republic of ChinaCorrespondence: Tianlin Wen; Wei Li, Email wentianlin@bucm.edu.cn; weilichn@126.comPurpose: Intervertebral disc degeneration (IDD) is considered the predominant cause of low back pain (LBP) and accounts for global disability and a substantial socioeconomic burden. Given the unsatisfactory outcomes of current treatment strategies, cartilage endplate-derived stem cells (CESCs) are increasingly used in intervertebral disc regeneration. However, comprehensive analyses on CESCs remain rare. Herein, we examined the biological functions and applications of CESCs in IDD.Methods: PubMed, Embase, and Cochrane Library databases were searched to identify studies focused on CESCs. Relevant information from included studies was extracted. Descriptive statistics were performed. Correlation analysis was conducted to determine the relationship among Web of Science (WoS) citations, Dimensions, and Altmetric Attention Score (AAS).Results: Twenty-six studies were included in this study. Most studies (n=20) isolated CESCs from humans, followed by rats (n=5) and rabbits (n=1). Twenty studies were performed in vitro, and the remaining six were implemented both in vivo and in vitro. The findings of this study provide insight into the biological properties of CESCs and clarify their potential application for intervertebral disc regeneration. There was a very high correlation between WoS and Dimensions citation count (p< 0.001, r=0.988).Conclusion: This study, for the first time, elaborates biological features of CESCs and analyzes their potential applications in regenerating intervertebral discs. CESCs may be promising candidates for protecting the intervertebral disc from degeneration and contributing to intervertebral disc regeneration.Keywords: intervertebral disc degeneration, low back pain, cartilage endplate-derived stem cells, stem cells, intervertebral disc